GRAPHICAL EXERGY ANALYSIS METHOD FOR OPTIMUM DESIGN AND OPERATIONS OF SEPARATION PROCESSES - KHOA, TA DANG (2012)
Enhancing the performance of energy savings is imperative to solve the issues of natural resources depletion and energy demand increase. Improvement of energy efficiency in chemical process industry leads to reduction of operations cost and environmental emission. In chemical plants, distillation and absorption are important separation processes that are widely used for product recovery and purification. These processes are energy intensive. Currently, exergy concept has gained renewed interest to analyse the performance of energy intensive processes. In this work, a general framework is proposed to establish the correlations between design and operations parameters to exergy lost of separation processes. A new graphical method, three dimensional exergy analysis diagram, is constructed from the general framework for optimisation of distillation and absorption columns. The diagram provides visualisation of the full energy savings potential and the path to achieve the optimum state of design and operations.